Pengelolaan Harta Dalam Tinjauan Q.S At-Takatsur - Ita Rukmanasari; Halimah Basri; Achmad Abubakar; Muh. Azka Fazaka Rifa’ih (TAFAQQUH, 2023)
This study aims to find out how the management of assets in the review of surah At-Takatsur, using library research methods or literature that refers to theories relevant to this research. The results in this study show that one of the actions that damage human life is to boast and boast of each other's greatness. It can deprive a person of the noble deeds he should be doing. Then boasting can make people go to the grave. Indeed, Allah strictly forbids man to boast because the reward for such actions is hell.